An empirical study of the effect of information technology expenditures on student achievement. Information technology, Productivity, Educational technology, Standardized testing, Internet in schools, Computers in schools - Alan R. Peslak (Information Research: An International Electronic Journal)
The impact of information technology on productivity in the private sector has been extensively researched. But the study of the impact of information technology expenditures in schools has been limited. This study of 1090 California schools and including over 6,000,000 students, attempts to address this issue through an analysis of IT expenditures at the school level and the effect on standardized reading and mathematics test scores. Thirteen other factors were also included in this analysis of the 2001-2002 academic year. Included are public school grades two through eleven. The results indicate that socio-economic status as measured by the percentage of students receiving free or reduced meals was the most significant factor in determining test scores. Also significant was percentage of fully qualified teachers. Information technology as measured by a number of factors did not show significant and positive effects on student performance.